The Level of Knowledge and Practice of Students Regarding Worship in Senior High Schools - Muhammad Zaidane A An Al Hafizi; Satrianis Satrianis; Muhammad Ikhsan; Puji Eka Putra; Utari Violanita; Syafrizal Syafrizal (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2022)
This study aims to find out how the level of knowledge and practice of students toward their worship. This study used a qualitative method with a phenomenological approach, data sources were taken from twenty informants through direct interviews, and all informants were active students at Madrasah Aliyah. All the results of the interviews were then Analysis Interactive Model Milles & Hubberman qualitative analysis. The results of this study are that the worship that is taught and accustomed to students is prayer, fasting, zakat, and Wudhu. Students' understanding of the stage of knowledge about worship already understand the meaning, conditions, and pillars. And also to find out the students' practice of this sholat. The knowledge stage of students is considered quite weak because most of the students cannot answer the questions given. Interestingly, students' practice of worship is classified as obedient and has become a daily habit. This shows that students' religious practice has become a personality (being/moral action) but is still weak in understanding (moral knowledge) and has not yet reached awareness (moral feelings).